Ocorrência e caracterização molecular de Giardia spp. em amostras fecais de cães naturalmente infectados em Santa Maria, RS - Osmari, Vanessa (2019)
Giardiasis is an important and prevalent zoonosis in dogs and humans, being caused by protozoa of the genus Giardia. The close relationship between pets and humans has many benefits, both physical, emotional and social. However, the presence of these animals without proper care may pose a risk to human health. As dogs have an important role in the cycle and transmission of Giardia duodenalis, the objective of this study was to verify the occurrence of the parasite in dogs in the city of Santa Maria, Rio Grande do Sul State (RS). Additionally, in this research, the objective was to carry out a molecular characterization and phylogenetic analyses of Giardia duodenalis. In this study, 230 samples of dog feces were collected from April to October 2018. Of these, 10 were from the routine of coproparasitological examinations performed at the Laboratory of Parasitary Diseases (LADOPAR) of the Federal University of Santa Maria (UFSM), 74 were collected in 3 commercial kennels and 166 were collected at the UFSM Veterinary University Hospital (HVU), all located in the city of Santa Maria, Rio Grande do Sul State, Brazil. All samples were submitted to the Faust coproparasitological technique, after which the total DNA extraction was carried out for the subsequent molecular analysis through the nested PCR technique. Afterwards, the positive samples in the nested PCR were sent for DNA sequencing. The sequences obtained from this study were compared with the sequences for the β-giardin (bg) gene deposited in GenBank and phylogenetic analyses were elaborated using the Neighbor-Joining method using bootstrap of 1000 replicates, where the evolutionary distances were calculated by the Jukes- Cantor method, and Mega X software was used to verify the relationship between assemblages or genotypes found in isolates. From the faecal samples analysed, there were no differences between the variables: diagnostic techniques, local, sex and age of the animals (p<0.05). In the Faust technique, 5.6% (13/230) of the samples were positive for the presence of Giardia spp. In the nested PCR, 4.3% (10/230) of the analysed samples were positive for the amplification of protozoan DNA. There was no significant difference in the results found (p>0.05), and there was no difference in the sensitivity of the tests used. The assemblages found in the positive samples were C and D, which are specific and frequently reported in dogs. In this way, we observed that Giardia duodenalis occurs in the dog populations evaluated in this study. Due to the proximity of dogs and their tutors, there may be the possibility of coinfection with other assemblages, thus increasing the risk of transmission of this zoonosis.